2020
DOI: 10.1039/d0na00093k
|View full text |Cite
|
Sign up to set email alerts
|

Nanolipogels as a cell-mimicking platform for controlled release of biomacromolecules

Abstract: We present studies of protein (insulin) efflux rates from nano-sized core–shell systems with a gelled core and a lipid bilayer (nanolipogels).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In this study, lipid concentration in the nanoparticles was determined by modified Stewart Assay through quantifying the phospholipids complex form with ammonium ferrothiocyanate 34 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, lipid concentration in the nanoparticles was determined by modified Stewart Assay through quantifying the phospholipids complex form with ammonium ferrothiocyanate 34 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, lipid concentration in the nanoparticles was determined by modified Stewart Assay through quantifying the phospholipids complex form with ammonium ferrothiocyanate 34 Quantitative cell entry was performed via flow cytometry (Guava® easyCyte 8HT Benchtop Flow Cytometer, Merck-Millipore). In this study, 100,000 FibroGRO cells were treated with NLG containing 0.0625 mM lipids with 0.1 mol % (1,2-dioleoyl-sn-glycerol-3-phosphoethanolamine-N-(carboxyfluorescein) (ammonium salt), Avanti) and then incubated 2 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…One of those approaches taken was using nanolipogel (NLG), in which the hydrophilic small-molecule drugs or biomolecules are encapsulated within the gelated core of the NLG, surrounded by a lipid bilayer ( Ramanathan et al, 2016 ; Guo et al, 2018 ; Cao et al, 2020 ). Current studies have demonstrated that NLGs has successfully been used to encapsulate and suppress the burst release of hydrophilic drugs and biomolecules, such as doxorubicin hydrochloride ( Yu et al, 2018 ), Dextran-Fluorescein Isothiocyanate (DFITC) ( Anselmo et al, 2015 ), maraviroc and tenofovir disoproxil fumarate ( Ramanathan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we adopted the design of PEGDA NLG ( Cao et al, 2020 ) for a mechanistic study on the release of encapsulated biomolecule, where inspiration was drawn from the concept of macromolecular crowding phenomenon in cells ( Ellis, 2001 ; Zhou et al, 2008 ; Soleimaninejad et al, 2017 ). It is known that the intracellular diffusion of proteins, or other biomolecules, in the cytoplasm can be hindered by a phenomenon loosely termed as “macromolecular crowding”, where intracellular organelles and macromolecules exhibit a crowding effect to hinders the diffusion of intracellular proteins.…”
Section: Introductionmentioning
confidence: 99%